A non-randomised controlled pilot study of clinical pharmacist collaborative intervention for community dwelling patients with COPD. (December 2018) - Hunt, Vicki; Anderson, Dave; Lowrie, Richard; Montgomery Sardar, Colette; Ballantyne, Susan; Bryson, Graeme; Kyle, John; Hanlon, Peter
Abstract UK, home-based patients with COPD receive specialist care from respiratory physicians, nurses, and general practitioners (GPs), but increasing complexity of therapeutic options and a GP/Nurse workforce crisis suggests merit in testing the role of home visits by a clinical pharmacist. We conducted a non-randomised intervention study with a contemporaneous comparator group, in Glasgow (Scotland). A clinical pharmacist (working closely with a consultant respiratory physician) visited patients with COPD living at home, assessing respiratory and other co-morbid conditions, and medicines then, with patient approval, agreed treatment modifications with a consultant physician. Comparator group-patients were drawn from another hospital out-patient clinic. Main outcomes were exacerbations during 4-months of follow-up and respiratory hospitalisations (number and duration) after 1 year. In the intervention group, 86 patients received a median of three home visits; 87 received usual care (UC). At baseline, patients in the intervention group were similar to those in UC in terms of respiratory hospitalisations although slightly younger, more likely to receive specific maintenance antibiotics/Prednisolone and to have had exacerbations. Sixty-two (72.1%) of the intervention group received dose changes; 45 (52.3%) had medicines stopped/started and 21 (24.4%) received an expedited review at the specialist respiratory consultant clinic; 46 (53.5%) were referred to other healthcare services. Over one-third were referred for bone scans and 11% received additional investigations. At follow-up, 54 (63.5%) of intervention group participants had an exacerbation compared with 75 (86.2%) in the UC group (p = 0.001); fewer had respiratory hospitalisations (39 (45.3%) vs. 66 (76.7%);p < 0.001). Hospitalisations were shorter in the intervention group. Pharmacist-consultant care for community dwelling patients with COPD, changed clinical management and improved outcomes. A randomised controlled trial would establish causality. COPD: At-home pharmacist visits improve health outcomes Clinical pharmacists, working in collaboration with respiratory specialists, can help people who live at home with chronic obstructive pulmonary disease (COPD) better manage their medications and symptoms. In a non-randomised pilot study, Richard Lowrie from the NHS Greater Glasgow and Clyde, UK, and colleagues found that patients with COPD who receive standard at-home care—which includes visits to GP surgeries and hospital-based respiratory out-patient clinics, and visits from respiratory specialist nurses—were more likely to experience exacerbations and need lengthy hospital stays than those who additionally received home visits from a clinical pharmacist. The pharmacist, in consultation with the patient's respiratory physician, often proposed medication changes and suggested additional testing or referrals that presumably explain the improved health outcomes. The authors conclude that a large, randomised trial is warranted to further evaluate the merits of this collaborative intervention for community dwelling patients with COPD.